Negative Shocks and Political Parties’ Territorial Demands: The Institutional Roots of Party Competition - Amat, Francesc; Rodon, Toni (Frontiers in Political Science, 2021)
Why do political parties set an extreme or a more moderate position on the territorial dimension? Despite previous works have paid recent interest on the dynamics of the political competition on the territorial dimension, we know much less about the factors that lead to a centrifugal or a centripetal party competition on the same dimension. In this article, we offer a new way of understanding it: we argue that parties’ policy position on the decentralization continuum not only depends on the level of territorial decentralization, but also on the credibility of the institutional agreement established through the country’s constitutional rigidity. If the original territorial pact does not guarantee that the majority group will have its “hands tied” so that it does not reverse the territorial agreement, political parties will have incentives to adopt more extreme positions on the territorial dimension. We test this argument with a dataset covering around 460 political parties clustered in 28 European countries from 1999 to 2019 and by exploiting the fact that the 2008 economic crisis unleashed a shock on the territorial design. Our results confirm our expectations. We show that both the federal deal and the credibility of the institutional arrangement through constitutional rigidity are necessary conditions to appease parties’ demands on the territorial dimension. Our results have important implications for our understanding of how institutions shape political competition along the territorial dimension.